EFEKTIVITAS PROMOSI TIKET.COM TERHADAP KEPUTUSAN WISATAWAN DOMESTIK DALAM PEMBELIAN TIKET PESAWAT MENUJU BALI - Luh Putu Riska Riana Paramita; I Wayan Suardana; I Made Sendra (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2018)
The purpose of this study is to determine the effectiveness of promotion Tiket.com through several stages, such as: identification dimensions empathy, persuasion, impact, and communication. Further reviewed how the effectiveness of promotion Tiket.com it can affect the decision to buy air tickets to Bali. Data collection techniques used obeservation, interviews, questionnaires, literature studies and documentation. Data collection techniques use non-probability sampling with accidental sampling procedure. The analysis technique used quantitative descriptive analysis and multiple linear regression analysis. The result of this study shows that the dimension of empathy (x1) has a positive and significant effect of 0.001 on buying decisions (y), persuasion dimension (x2) has a positive and significant effect of 0.001 on buying decisions (y), impact dimension (x3) significant 0,041 to the buying decision (y) and the last dimension of communication (x4) have a positive and significant effect of 0.000 on buying decision (y). From the EPIC model is the face of communication is the biggest factor influencing the decision of tourists to buy ticket through the website Tiket.com. This is because the communication contained in promotion Tiket.com easy to understand and attached to the memory of tourists to use the website Tiket.com when buying air tickets if want to travelling.